PSYCHOLOGICAL CONTENT OF OPTIMISM IN THE CONTEXT OF FORMATION OF THE CONSTRUCTIVE LIFE POSITION OF THE PERSONALITY - Назаренко, Наталія Анатоліївна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The article highlights the results of theoretical and empirical study of the psychological content of optimism in the context of the formation of a constructive life position of the personality. Constructive life position of the personality is determined by the formation of views, judgments, a system of appraisals, knowledge and beliefs in relation to oneself and the world at large, awareness of own value and values of others, motivation to build and improve own life position, validity of the decision made on the determination of a life position and ways of its achievement depends on the success of interaction with others. Optimism as an important psychological characteristic, according to the model of behavioral self-regulation, helps a person to make efforts aimed at overcoming difficulties in achieving the set goals. The purpose of the article was to highlight the results of theoretical and empirical research and justify the psychological content of optimism and its meaning in the context of the constructive life position. An analysis of empirical research was presented, the hypothesis of which became setting that the level of optimism influences the choice of life position of student youth. For the empirical study, the techniques of E. Berne's "Life position of the personality" and the questionnaire for determining the dispositional optimism (LOT) of C. Carver, M. Scheyer in the adaptation of D.A. Tsering, K. Yevnina were selected. The data obtained in the course of the study make it possible to confirm our hypothesis that the level of optimism can be a necessary component in formation of the constructive life position of the student's personality. The conclusions substantiate the need to develop psychological and pedagogical means of developing a constructive life position and to create the necessary conditions for their implementation both in school education and in the system of higher educational institutions